👤

2,6-2, (3)+1, (6)+(2,3-0,9)


Răspuns :

 2,6-2, (3)+1, (6)+(2,3-0,9)
2,6=
[tex] \frac{26}{10} [/tex]
2,(3)=[tex] \frac{123-12}{90} [/tex]=[tex] \frac{111}{90} [/tex]
1,(6)= (16-1):9=15:9=5:3=[tex] \frac{5}{3} [/tex]
2,6=
[tex] \frac{26}{10} [/tex] 
 2,3= [tex] =\frac{23}{10} [/tex]
 0,9=[tex] \frac{9}{10} [/tex]

[tex] \frac{26}{10} [/tex]-[tex] \frac{111}{90} [/tex]+[tex] \frac{5}{3} [/tex]+( [tex] \frac{23}{10} [/tex]-[tex] \frac{9}{10} [/tex])=aducem la numitor comun(=90)
amplificam primul termen cu 9, al doilea cu 1, al treilea  cu 30, si ultimul cu 9
(9×26-111+30×5+14×9):90=(234-111+150+126):90=399:90=[tex] =\frac{399}{90} [/tex]